TLR4 induced Wnt3a-Dvl3 restrains the intensity of inflammation and protects against endotoxin-driven organ failure through GSK3β/β-catenin signaling. (February 2020) - Yang, Dongqiang; Li, ShuJian; Duan, Xiaoxian; Ren, Junling; Liang, Shuang; Yakoumatos, Lan; Kang, Yi; Uriarte, Silvia M.; Shang, Jia; Li, Wei; Wang, Huizhi
Highlights: TLR4 activation enhances the expression of Wnt3a and Dvl3 in innate immune cells. Wnt3a-Dvl3 reduces pro-inflammatory cytokine production via β-catenin/NF-κB pathway. Wnt3a restrains inflammation intensity and protects mice from lethal endotoxemia. Wnt3a signaling could be a target to manipulate the intensity of inflammation. Abstract: Background: Accumulating evidence suggests a regulatory role of Wnt proteins in innate immune responses. However, the effects of Wnt3a signaling on TLR4-mediated inflammatory responses are controversial and the signaling crosstalk between TLR4 and Wnt3a remains uncertain. Methods: Gain- and Loss- of function approaches were utilized to determine the function of Wnt3a signaling in TLR4-mediated inflammatory responses. Cytokine production at protein and mRNA levels and phosphorylation of signaling molecules were measured by ELISA, qRT-PCR, and Western Blot, respectively. Endotoxemia mouse model was employed to assess the effect of Wnt3a on systemic inflammatory cytokine levels and neutrophil infiltration. Results: LPS stimulation leads to an increase of Wnt3a expression and its downstream molecule, Dvl3, in primary monocytes. Inhibition or silence of Wnt3a or Dvl3 significantly increases the production of pro-inflammatory cytokines (IL-12, IL-6, TNFα), robustly reduces β-catenin accumulation, and enhances the phosphorylation of NF-κB P65 and its DNA binding activity. These results were confirmed by multiple gain- and loss- of function approaches including specific siRNA and ectopic expression of Dvl3, GSK3β, and β-catenin in monocytes. Moreover, in vivo relevance was established in a murine endotoxin model, in which Wnt3a inhibition enhances the inflammatory responses by augmenting the systemic pro-inflammatory cytokine levels and neutrophil infiltration. Conclusions: TLR4 activation promotes Wnt3a-Dvl3 signaling, which acts as rheostats to restrain the intensity of inflammation through regulating GSK3β-β-catenin signaling and NF-κB activity. General significance: Wnt3a-Dvl3-β-catenin signaling axis could be a potential interventional target for manipulating the direction and intensity of inflammatory responses.